Archaeal and bacterial communities in three alkaline hot springs in Heart Lake Geyser Basin, Yellowstone National Park - De León, Kara B.; Gerlach, Robin; Peyton, Brent M.; Fields, Matthew W. (Frontiers in Microbiology, 2013)
The Heart Lake Geyser Basin (HLGB) is remotely located at the base of Mount Sheridan in southern Yellowstone National Park, Wyoming, USA and is situated along Witch Creek and the northwestern shore of Heart Lake. Likely because of its location, little is known about the microbial community structure of springs in the HLGB. Bacterial and archaeal populations were monitored via small subunit (SSU) rRNA gene pyrosequencing over 3 years in 3 alkaline (pH 8.5) hot springs with varying temperatures (44°C, 63°C, 75°C). The bacterial populations were generally stable over time, but varied by temperature. The dominant bacterial community changed from moderately thermophilic and photosynthetic members (Cyanobacteria and Chloroflexi) at 44°C to a mixed photosynthetic and thermophilic community (Deinococcus-Thermus) at 63°C and a non-photosynthetic thermophilic community at 75°C. The archaeal community was more variable across time and was predominantly a methanogenic community in the 44°C and 63°C springs and a hyperthermophilic community in the 75°C spring. The 75°C spring demonstrated large shifts in the archaeal populations and was predominantly Candidatus Nitrosocaldus, an ammonia-oxidizing crenarchaeote, in the 2007 sample, and almost exclusively Thermofilum or Candidatus Caldiarchaeum in the 2009 sample, depending on SSU rRNA gene region examined. The majority of sequences were dissimilar (≥10% different) to any known organisms suggesting that HLGB possesses numerous new phylogenetic groups that warrant cultivation efforts.